Modern Islamic Boarding School Education Concepts and Systems - Budiman, Budiman; Budianti, Yusnaili; MH Pasi, Kamaluddin (Budapest International Research and Critics University, 2022)
The aims of this study are to find out modern islamic boarding school education concepts and systems. This study used qualitative research method. The result of this study shows that the concept and system of modern pesantren education from the beginning of its formation consisting of goals, curriculum, methods, educators, students, and the environment, is the result of the renewal of Islamic education. The concept of modern pesantren education is the integration of education between religious and general education, whether it is with the concept of madrasa in pesantren, or original modern pesantren by applying the madrasa style. The point is to teach Islamic religious sciences, accompanied by general education. The basis of modern pesantren education remains at the core of Islamic teachings. The desired educational goal is to create intellectual scholars, with good religious knowledge but also have skills in the fields of science, technology, and other fields that are beneficial to society. Has a curriculum that contains religious materials, as well as general subject matter such as exact science, science, social studies, foreign languages, plus a non-formal education curriculum in the form of supporting activities